Feed Management And Diversification Forage In The Galang Kangin Goat Farm Group, Apuan Village, Baturiti Tabanan - I Gusti Agus Maha Putra Sanjaya; I Nyoman Kaca; Ni Ketut Etty Suwitari; I Putu Krismayana; Made Pradnyagitha Harum Devani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Goats are potential livestock in Apuan Village, but their development is stillconstrained by the variety of forage available. The community service partner is theGalang Kangin Goat Group. The contribution provided is education about themanagement of providing superior forage that suits the needs of goats, plantingsuperior forage, and training in calculating the nutrients of the ration that will begiven daily. The activity was conducted on 22 June 2024 using the activeparticipation method. The out put of this activity is that farmers are able to choosesuperior forage as goat feed, increase the variety of forage, and are able tocalculate daily nutrition so that the goats they keep can grow and reproducequickly..